PENGARUH ATRIBUT PRODUK BATIK TERHADAP KEPUTUSAN KONSUMEN MEMBELI PRODUK BATIK - Retnowati . (Jurnal Ekonomi Dan Bisnis, 2015)
Batik product is an original product of Indonesia which is unique, attractive, and highly civilized. Therefore,research on the decision to buy a product made of batik is very interesting. The purpose of this study was toexamine the effect of product attributes that includes batik price, product quality and product style or motive ofbatik product purchasing decisions on the Pekalongan City.The data used are primary data collected through survey method using questionnaire and tested for validity andreliability. The sample was obtained using a convenience sampling method and then analyzed using multipleregression techniques to test the hypothesis.The results of this study indicate there is significant influence variable pricing, product quality, and style ormotive to the decision to purchase products either partially or simultaneously, so that hypotheses 1, 2, 3 and 4are supported by the results of this study. While the decision to buy the product of batik can be explained by 4variables batik attribute is 95%.Keywords: batik product, batik price, batik quality, product purchasing decisions